2018
DOI: 10.1038/s41366-018-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietitian-led lifestyle modification programme for obese Chinese adolescents with non-alcoholic fatty liver disease: a randomized controlled study

Abstract: A dietitian-led lifestyle modification intervention reduced IHTC, BMI z-score and body fat in obese Chinese adolescents with NAFLD. To sustain the effect of this intervention, regular parental and paediatrician involvement may be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(72 citation statements)
references
References 26 publications
0
72
0
Order By: Relevance
“…Currently, the main therapeutic strategies for NAFLD depend on lifestyle changes as there is no specific pharmacological option for the treatment of NAFLD [ 17 19 ]. But due to poor adherence to life style modification, finding new therapeutic agents to treat NAFLD or preventing its progression has attracted many interests.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main therapeutic strategies for NAFLD depend on lifestyle changes as there is no specific pharmacological option for the treatment of NAFLD [ 17 19 ]. But due to poor adherence to life style modification, finding new therapeutic agents to treat NAFLD or preventing its progression has attracted many interests.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the completion rates of the studies, Agustini et al [29] and Schwimmer et al reported 100%, Ramon-Krauel et al [27] reported 94%, Jin et al [28] reported 91.7%, while Goss et al [31] reported only 78%. Of the eligible studies, six RCTs evaluated the effects of dietary modifications in pediatric NAFLD patients [26][27][28][29][30][31], three evaluated the effects of diet plus exercise modification [25,32,33], whereas no studies assessed exercise as the sole intervention. In this category, only one study was analyzed [34], which assessed the effects of different types of exercise, although dietary and psychological support were also given to both groups.…”
Section: Interventions Based On Dietmentioning
confidence: 99%
“…Three studies [25,32,33] evaluated the effects of diet plus physical activity interventions on NAFLD. Study characteristics are shown in Table 2.…”
Section: Interventions Based On Diet Plus Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations